Implementasi Program Pengendalian Kematian Bayi di Kabupaten Musi Rawas Utara - Suciati, Dina; Sari Murni, Nani; Wahyudi, Arie; Suryanti, Dewi (Avicenna: Jurnal Ilmiah, 2024)
Background: The infant mortality rate is an indicator of the success of maternal and child health programs. The lower the infant mortality rate indicates the success of developing family health. Based on the 2020-2024 RPJMN, the infant mortality rate in 2019 (SDKI, 2017) was 24 per 1000 population births, it is hoped that it will decrease to 16 per 1000 population births in 2024. Health status and education levels have improved, but have not yet reached the entire population. Maternal and infant mortality is still high. The capacity of health workers, the maternal referral system, and the management of maternal and child health services, as well as reproductive health services, are not yet running optimally. Method: This research method is qualitative research using descriptive analysis. Research informants are divided into two, namely supporting informants and key informants. The number of informants was 12 people consisting of 0 key informants and 2 supporting informants. Results: The results of the research show that the background to the implementation of the program is not yet understood by health workers, while the goals and objectives of the program are in accordance with the regulations of the Ministry of Health. The implementation of the program has been carried out well, there is support from across sectors and across programs, but there are obstacles due to the characteristics of the community itself. The results of achieving SPM services for newborns have not yet reached 100%. The IMR (Infant Mortality Rate) of North Musi Rawas District is 8.7 per 1000 population, below the central government target of 16 per 1000 population. Conclusion: So that officers are given training so they can understand the background of program implementation, increase activities to increase targets, guide policies in carrying out program implementation, look for ways to overcome obstacles, and improve service outcomes for newborns. Keywords: Infant Mortality Rate, Programs, Maternal and Child Health